A dermatopathic Juvenile Dermatomyositis; An Unexpected Case in Childhood - Yeganeh, Mehrnoush Hassas; Ahmadi, Pooria; Nilipour, Yalda; Khorshidi, Mohaddeseh Sadat Musavi; Sinaei, Reza; Fathi, Mohammad Reza; Shiari, Reza (Iranian Journal of Child Neurology, 2020)
Abstract Juvenile dermatomyositis (JDM) is a rare idiopathic inflammatory disease which usually presents with skin rashes along with muscle weakness. We report a case of JDM in a 10- year-old girl with no skin manifestations. She was presented with progressive muscle weakness and fatigue. Further laboratory investigation along with a muscle biopsy confirmed the diagnosis of Adermathopathic Juvenile Dermatomyositis. The patient was treated with intravenous immunoglobulin, corticosteroids, methotrexate, hydroxychloroquine, pamidronate, and Rituximab. Following treatment, patients symptoms subsided and she gained normal muscular strength over the course of a year.